Images of extreme weather: symbolising human responses to climate change - Nerlich, Brigitte; Jaspal, Rusi (Taylor & Francis, 2013)
Extreme weather events have been increasingly in the news, accompanied by images. At the end of 2011, when such reports were ever present, the International Panel on Climate Change published a draft report on extreme weather and climate change adaptation. This report itself was covered in the news and illustrated with images. Some of these depicted ‘extreme weather’, in particular with relation to floods, droughts and heat waves, hurricanes and ice/sea-level rise. For this article, these images were studied using visual thematic analysis, with a focus on examining the way they may symbolise certain emotional responses, such as compassion, fear, guilt, vulnerability, helpless, courage or resilience. Climate change communicators have examined the way that evoking such emotions in verbal communication can lead to engagement or disengagements with the topic of climate change. However, while researchers have also become increasingly interested in climate change images, they have not yet studied them with respect to symbolising certain emotions. Various typologies of images have been proposed in the past, distinguishing, for example, between human and natural impact images or iconic and geographically specific images. The images studied here do not neatly map onto these distinctions. They symbolise human suffering and loss and they are sometimes geographically and socially distinctive, but they are also iconic of climate change and they are symbols of its natural impacts. They all, to some extent, symbolise helplessness and may thus lead to disengagement rather than engagement with the issue of climate change.